The Effect of Self-Hypnosis on Mental Health Teenagers are Addicted to Social Media - Perak Maruli Asi Hutagalung; Rugun Togianur Lingga; Verawaty Fitrinelda Silaban (Indonesian Journal of Global Health Research, 2026)
Social media addiction is a worrying phenomenon among adolescents due to its negative impact on mental health, such as increased stress, anxiety, and depression. Self-hypnosis is a relaxation technique that can help individuals independently control negative thoughts and emotions. This study aims to determine the effect of self-hypnosis on the mental health of adolescents experiencing social media addiction. This study used a quasi-experimental design with a one-group pre-test and post-test approach. The sample consisted of 90 eleventh-grade students at SMA Negeri 2 Sidikalang, selected using systematic random sampling. Measurements were taken before and after the self-hypnosis intervention. In this study, to measure the mental health of adolescents, an instrument was used in the form of the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS).  Data were analyzed using the Wilcoxon Signed Rank Test. Before the intervention, most respondents had a moderate level of mental health (83.3%), while after the intervention, this increased to 58.9% in the high category. The Wilcoxon test showed a significant difference between mental health scores before and after the intervention (Z = -7.620; p = 0.000). Cohen's d value of 1.40 indicates a very strong effect, indicating that self-hypnosis is effective in improving the mental health of adolescents with social media addiction. Self-hypnosis has been shown to have a significant effect on improving adolescent mental health. This technique can be used as a non-pharmacological intervention to reduce the negative impacts of social media addiction, increase calmness, and strengthen self-control.